Gelation and melting of gelatin. - Clegg, Stuart Mark (Cranfield University, 1990)
Chiroptical, rheological and thermodynamic studies have been undertaken to investigate temperature-induced changes in the ý molecular organisation of gelatin. From the results obtained, a unified model for gelation and melting has been developed, and tested using Monte Carlo computer simulation. The temperature at which gelatin gels are formed has a major influence on the properties of the resulting network, with higher curing temperatures conferring increased thermal stability. In particular, gels formed by sequential curing at two different temperatures show biphasic melting. This is explained in terms of a temperature-dependence of helix length within the junction zones of the gel, and quantified by considering end-effects in the thermodynamics of helix stability. Measurements of 'initial slope' kinetics, performed over a broad concentration range, showed first-order kinetics at low gelatin concentrations, while at higher concentrations a second-order process was also evident. The results are interpreted as triple-helix nucleation at metastable 'hairpin turns' in one chain (bringing two chain segments into close proximity) together with a third strand from either the same chain (first order) or a different chain (second order). From simple geometric considerations, the maximum length of intermolecular helices ( which contribute to the gel network) is greater than that of twasted 9 intramolecular structures, giving a qualitative explanation of the increased strength of gels formed by precuring at higher temperatures (where only long helices are stable) over those quenched directly to low temperature. Monte Carlo simulation incorporating an initial assumption that helix propagation is rapid and proceeds to geometric limits gave unrealistic helix lengths and simulated melting profiles, and was replaced by the assumption that cis-trans isomerisation of peptide bonds is the controlling factor in helix propagation. Using the latter assumption, most aspects of the observed behaviour were successfully reproduced using program variables set within realistic ranges or, where possible, fixed at experimentally-determined values. In particularg the co-operativity of the simulated melting process was critically dependent on the value of a parameter x (the number of triplet units within each helix incapable of participating in bonding, due to end-effects), with a value of x=1 giving the best fits with experiment (consistent with accepted bonding patterns for the collagen triple helix). Other key parameters were the midpoint temperature for melting of the parent collagen, which gave best agreement when set at 37-38"C, and t6e proportion of cis peptide residues present in disordered gelatin chains, with an optimum lower limit of 0.15. Using these values, the simulation reproduced, with excellent precision, the helix fraction and melting profile of gels formed over a wide range of quench temperatures, and gave an acceptable approximation to the form of reaction progress curves obtained for helix formation. The biphasic melting of samples held at intermediate temperature before final quenching was also modelled realistically.